2022
DOI: 10.1002/adsc.202200751
|View full text |Cite
|
Sign up to set email alerts
|

Gold‐Catalyzed Oxygen Transfer to Alkynylsulfones: A Diazo‐Free Route to 4‐Sulfonyl‐1,3‐Oxazoles

Abstract: The gold-catalyzed annulation of alkynylsulfones, involving pyridine N-oxides (as O-atom transfer reagents) and nitriles (as C=N synthons), comprises a diazo-free route to valuable 4-sulfonyl-1,3-oxazoles. This reaction operates under relatively mild conditions (IPrAuNTf 2 5 mol %, rt or 60 °C), and a number of functionalities was compatible (35 examples; 14-95%). In most cases, the SO 2 fragment, which is typically expulsed in the previously reported Au-catalyzed O-transfers to alkynylsulfones, retains in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…[28][29][30][31][32][33][34] Owing to the high polarization, the ynamide C � C triple bond is sensitive to the action of various nucleophilic reagents. Additionally, electrophilic activation of ynamides by Brønsted [35,36] or Lewis acids (especially gold-containing compounds [37][38][39] ) allows the selectivity control of ynamide-based transformations. In the vast majority of cases, the amide site of ynamides is retained in the reactions, and all these make ynamides ideal candidates for the development of new synthetic routes to N-heterocycles and also to other useful amino-substituted products.…”
Section: Introductionmentioning
confidence: 99%
“…[28][29][30][31][32][33][34] Owing to the high polarization, the ynamide C � C triple bond is sensitive to the action of various nucleophilic reagents. Additionally, electrophilic activation of ynamides by Brønsted [35,36] or Lewis acids (especially gold-containing compounds [37][38][39] ) allows the selectivity control of ynamide-based transformations. In the vast majority of cases, the amide site of ynamides is retained in the reactions, and all these make ynamides ideal candidates for the development of new synthetic routes to N-heterocycles and also to other useful amino-substituted products.…”
Section: Introductionmentioning
confidence: 99%
“…Transformations that lead to rearrangements with a tethered nucleophilic functional group can rapidly generate multiple cyclic frameworks with high sp 3 ‐content and an increasing number of stereocenters in a single operation. Such features render homogenous gold catalysis attractive for optimizing molecular complexity [10–21] . We expect that gold carbene chemistry in conjunction with rearrangement/migration offers an efficient approach to propellane‐type scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Such features render homogenous gold catalysis attractive for optimizing molecular complexity. [10][11][12][13][14][15][16][17][18][19][20][21] We expect that gold carbene chemistry in conjunction with rearrangement/migration offers an efficient approach to propellane-type scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we have shown that alkynylsulfones can act as synthetic equivalents to β-ketosulfones. , In view of the high degree of polarization of the CC bonds, the reactions of alkynylsulfones are highly regioselective. On the contrary, the use of metal-based activators (especially gold complexes) , allows the conductance of the reactions, involving alkynylsulfones, under relatively mild conditions. On the basis of all of these data, we hypothesized that the reaction of alkynylsulfones with 2-amino-substituted arylcarbonyls could be a convenient alternative to FS in the context of the modular one-step synthesis of 3-sulfonylquinolines (Scheme C).…”
mentioning
confidence: 99%
“…Very recently, we have shown that alkynylsulfones can act as synthetic equivalents to β-ketosulfones. 35,36 In view of the high degree of polarization of the C�C bonds, the reactions of alkynylsulfones are highly regioselective. On the contrary, the use of metal-based activators (especially gold complexes) 37,38 allows the conductance of the reactions, involving alkynylsulfones, under relatively mild conditions.…”
mentioning
confidence: 99%